Copper coins from the Bolgar settlement as a historical source - Khramchenkova R.Kh.; Mukhametshin D.G.; Sitdikov A.G.; Fedan P.V. (Золотоордынское обозрение)
Research objectives: The present work is devoted to the study of the temporal features of the collection of copper coins found at the Bolgar settlement. Research materials: 88 coins of various rulers and minted households of the wide time span of the XI–XV centuries were used for a comparative analysis. The chemical composition of the metal was taken as the main determining element. Results and novelty of the research: According to this research, ten groups with characteristic elemental ratios were identified. Interdisciplinary research, including historical-numismatic and chemical analysis, allows one to make a number of assumptions and conclusions regarding the copper raw materials which served as material for minting coins, as well as regarding the monetary policy of the state of the Golden Horde. The presented scientific research is pioneering in this area since a study of the chemical composition of the coins circulating in the Volga region has heretofore not been carried out.